Preparation method of coal-based red fluorescent carbon dots
By using lignite and mixed acid pretreatment combined with hydraulic cavitation technology to prepare red fluorescent carbon dots, the problem of single fluorescence of coal-based carbon dots in the prior art is solved, and the pleochroism and fluorescence performance are improved, making it suitable for a variety of applications.
Patent Information
- Application Number
- CN202511265213.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-09-05
AI Technical Summary
The fluorescence of existing coal-based carbon dots is generally blue, which makes it difficult to extend to applications such as multicolor fluorescence imaging and long-wavelength detection. Furthermore, chemical oxidation methods weaken the surface groups of carbon dots, affecting their fluorescence performance.
Using lignite as raw material, red fluorescent carbon dots were prepared by pretreatment with mixed acid and ammonia followed by hydrocavitation technology to remove them, retaining abundant surface functional groups and regulating the band structure.
Red fluorescent carbon dots were prepared, expanding the fluorescence wavelength range and enriching the polychromaticity. This method is applicable to fields such as full-view high-definition live imaging, flexible quantum dot displays, and warm white LED light sources, and is environmentally friendly and low-cost.
Smart Images

Figure CN120888295A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of coal-based carbon nanomaterials, and in particular to a preparation method of coal-based red fluorescent carbon dots. BACKGROUND
[0002] Carbon dots not only have excellent biocompatibility, but also have excellent fluorescence characteristics and electron transport capacity, and have broad application potential in panoramic high-definition live imaging, flexible quantum dot display, warm white LED light source, full-spectrum catalysis and other fields. These applications are mostly based on the multicolor properties of carbon dots, among which the representative of red carbon dots is particularly prominent. Therefore, screening of industrial raw materials with suitable structure and stable performance, and developing industrialized preparation processes matching the structure, are the core keys to promoting the large-scale application of multicolor carbon dots.
[0003] Coal, as a common industrial product, not only has abundant reserves and low cost, but also has unique advantages due to its microstructure characteristics. From the structure, coal is composed of graphite crystallites containing conjugated sp 2 hybrid carbon, which forms a three-dimensional cross-linked macromolecule through interactions such as short aliphatic bonds and ether bonds. Among them, the graphite crystallites exist in the form of zero-dimensional carbon nanoparticles, which are highly similar to the conjugated carbon core structure of carbon dots; and the chemical bonds in the three-dimensional cross-linked network and the functional groups formed after the breakage of the chemical bonds can provide carbon dots with abundant amorphous surface groups. Based on the above characteristics, coal becomes an ideal raw material for industrialized preparation of carbon dots.
[0004] Currently, the mainstream preparation method of coal-based carbon dots is to use various oxidizing agents to cut off the cross-linking bonds between graphite crystallites in coal, so as to release carbon nanoparticles (i.e. carbon dots), such as mixed acid (H2SO4 / HNO3), HNO3, H2O2, etc. In addition, some existing technologies also propose new oxidation strategies, such as Fenton reagent and high ferrate pre-oxidation + hydrogen peroxide, etc. However, these oxidation methods not only cut off the cross-linking bonds to release carbon nanoparticles, but also indiscriminately oxidize various functional groups and dangling bonds on the surface of graphite crystallites. This non-selective oxidation significantly reduces the types and quantities of surface groups of carbon dots, and further seriously weakens the surface state fluorescence of carbon dots. As a result, the fluorescence of existing coal-based carbon dots mainly comes from the conjugated carbon core. Due to the small conjugated π domain, the energy band gap caused by the quantum confinement effect is wide, which makes the radiation fluorescence energy high, and the spectrum is concentrated in the short-wave region, showing a common blue fluorescence characteristic. This short-wave blue fluorescence faces a double application dilemma: on the one hand, it is easily disturbed by the autofluorescence of biological tissues, and on the other hand, it may cause damage to normal matrix, which greatly limits the application expansion of coal-based carbon dots in multicolor fluorescence imaging, long-wavelength detection and other scenarios. SUMMARY
[0005] The present application aims to provide a preparation method of coal-based red fluorescent carbon dots to solve the problems of the prior art.
[0006] To achieve the above-mentioned purpose, the present application provides the following solutions.
[0007] One of the technical solutions of the present application is a preparation method of coal-based red fluorescent carbon dots, comprising the following steps:
[0008] The lignite is added into a mixed solution of concentrated sulfuric acid and concentrated nitric acid, and after a first mixing reaction, the pH is adjusted to neutral by using ammonia water, and a second mixing reaction is performed to obtain a coal sample;
[0009] The coal sample is added into water to prepare a lignite mixed solution, and then the lignite mixed solution is subjected to cavitation stripping treatment to obtain the coal-based red fluorescent carbon dots.
[0010] Further, the particle size of the lignite is ≤200 mesh.
[0011] Further, the mass ratio of the lignite to the mixed solution of concentrated sulfuric acid and concentrated nitric acid is 1:1-1:4.
[0012] Further, the mass ratio of the lignite to the mixed solution of concentrated sulfuric acid and concentrated nitric acid is 1:2-1:4.
[0013] Further, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1:2-1:10.
[0014] Further, the rotation speed of the first mixing reaction is 600-1500 r / min, and the time is 8-12 h.
[0015] Further, the rotation speed of the second mixing reaction is 600-1000 r / min, and the time is 8-10 h.
[0016] Further, the volume ratio of the coal sample to water is 5-50 g:1 L.
[0017] Further, the flow rate of the cavitation stripping treatment is 1-200 L / h, and the time is 8-10 h.
[0018] Further, the flow rate of the cavitation stripping treatment is 25-75 L / h.
[0019] Further, after the second mixing reaction, a filtration step is further included; the filtration includes filtering with a microporous filter membrane with a pore size of 0.1-0.6 μm.
[0020] Further, after the cavitation stripping treatment (i.e. hydrodynamic cavitation technology), a step of filtering to remove large particles is further included; the filtration includes filtering with a microporous filter membrane with a pore size of 0.1-0.6 μm.
[0021] The main role of filtration is to filter out large coal samples remaining after the reaction, and carbon dots remain in the aqueous solution.
[0022] Further, the cavitation stripping treatment is carried out in a cavitation device provided with a Venturi tube.
[0023] The cavitation stripping treatment (i.e. the hydrodynamic cavitation technology) adopted in the present application generates cavitation bubbles during the process, which release phase change energy through shock waves, micro-jets, local hot spots and hydroxyl radicals at the moment of collapse, significantly strengthening the physical and chemical processes in the fluid, and effectively cutting the cross-linking bonds between the graphite crystallites in the coal, so that the graphite crystallites are released as carbon dots.
[0024] The cavitation stripping treatment (i.e. the hydrodynamic cavitation technology) adopted in the present application has the following advantages: on the one hand, it does not require the use of any chemical reagents, completely avoiding the ecological environmental burden; on the other hand, the device structure is simple, the cost is low, the operation is convenient and easy to industrialize, and it shows great industrialization potential. More importantly, unlike the chemical method which cuts the cross-linking bonds through oxidation-reduction reaction, the hydrodynamic cavitation technology mainly relies on physical actions such as high-pressure shock waves and micro-jets to mechanically destroy the cross-linking bonds, which can maximize the preservation of aliphatic hydrocarbon bonds, ether bonds and other bonds on the surface of carbon dots as functional groups, providing rich surface state fluorescence for carbon dots.
[0025] The present application selects lignite with low degree of coalification, rich surface functional groups and less aromatic ring structure as raw material (lignite element content: carbon 68.94%, oxygen 25.40%, silicon 2.82%, aluminum 2.19%, iron 0.65%; among them, the carbon element is significantly lower than that of bituminous coal 82.40%, and the oxygen content is significantly higher than that of bituminous coal 12.46%, which indicates that lignite contains rich oxygen-containing functional groups on the surface), first pretreats the coal sample with a reagent combination of mixed acid and ammonia water, and then strips the coal sample treated by the hydrodynamic cavitation technology, to finally prepare coal-based carbon dots with red fluorescence characteristics.
[0026] The specific principle is as follows:
[0027] The lignite has low degree of coalification, retains a large amount of incompletely decomposed plant residues (such as lignin, cellulose), has short molecular chains, and contains rich functional groups such as hydroxyl (-OH), carboxyl (-COOH) and methoxyl (-OCH3); at the same time, its aromatic ring structure is underdeveloped, and is mainly a low-polymerization degree cyclic structure with long side chains. These structural characteristics (rich surface functional groups and low-polymerization aromatic ring system) provide a diverse material basis for the surface state luminescence of carbon dots.
[0028] When the mixed acid and ammonia water reagent combination is used for lignite pretreatment, the mixed acid opens the aromatic ring structure through oxidation, and the ammonia water attaches specific red fluorescent groups to the coal surface through nitrogen doping. These groups form new surface state energy levels in the coal-based carbon dots, not only increasing the number of energy levels in a single band, but also narrowing the energy band gap, which promotes the reduction of radiation fluorescence energy, ultimately giving the coal-based carbon dots red fluorescence emission characteristics.
[0029] When the lignite mixed liquid flows through the Venturi tube, cavitation reaction is triggered and huge phase change energy (about 1-10 18 kW / m 3 ) is released, which is specifically in the form of shock wave (propagation speed 2000 m / s), microjet (450 MPa high pressure and 3.5 kPa high shear force) and local thermal effect (2000-6000 K hot spot). The above physical and mechanical effects can effectively cut off the three-dimensional cross-linking bonds in the coal body, promote the exfoliation of graphite microcrystals into water to form carbon dots. At the same time, the above physical effects have little effect on the groups on the surface of the coal powder, and the original functional groups or functional bonds can be retained on the surface of the carbon dots, thereby realizing the regulation of the energy band structure of the carbon dots.
[0030] The second technical solution of the present application is a coal-based red fluorescent carbon dot prepared by the above preparation method.
[0031] The third technical solution of the present application is the application of the above coal-based red fluorescent carbon dot in the preparation of fluorescent materials or electron transport materials.
[0032] The present application discloses the following technical effects:
[0033] (1) The coal-based carbon dots with red fluorescence characteristics prepared by the present application solve the common problem that the coal-based carbon dots prepared by the current mainstream chemical oxidation exfoliation method generally have blue fluorescence, and provide a new technical path and solution for expanding the fluorescence wavelength range of coal-based carbon dots and enriching their multicolor.
[0034] (2) The present application uses a mixed reagent of mixed acid + ammonia water to pretreat lignite samples, so that specific red fluorescent groups are doped or attached, and then uses hydrodynamic cavitation technology to exfoliate and obtain coal-based red fluorescent carbon dots while retaining these specific groups, providing a method with industrial production potential for applications in full HD live imaging, flexible quantum dot display, warm white LED light source, full spectrum catalysis and other fields.
[0035] (3) The preparation method of the present application has the advantages of green, environmental protection, low cost and the like, and has the potential for industrial application. BRIEF DESCRIPTION OF DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed in the embodiments. Obviously, the drawings in the following description only constitute some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained from these drawings without any creative effort.
[0037] Figure 1 Fluorescence curves of the aqueous solution of the coal-based red fluorescent carbon dots prepared in Example 1 under different excitation lights and a photo under a 356 nm ultraviolet light (inset);
[0038] Figure 2 Transmission electron microscope image of the coal-based red fluorescent carbon dots prepared in Example 1;
[0039] Figure 3 Fluorescence curves of the aqueous solution of the coal-based fluorescent carbon dots prepared in Comparative Example 1 under different excitation lights and a photo under a 360 nm ultraviolet light (inset);
[0040] Figure 4 Fluorescence confocal microscope photo of the microorganism Shewanella labeled with the carbon dots prepared in Example 1 in Effect Example 1. DETAILED DESCRIPTION
[0041] The various illustrative embodiments of the present application will now be described in detail below. The following description is not to be considered to be limiting of the present application, but rather a description of certain aspects, features and embodiments of the present application.
[0042] It should be understood that the terms used in the present application merely describe particular embodiments and are not intended to limit the present application. In addition, for the numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed. Each smaller range within any stated range or within any stated intermediate value and any other stated value or intermediate value within the stated range is also included in the present application. The upper limit and the lower limit of these smaller ranges can be included or excluded independently.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application pertains. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All publications mentioned in the specification are incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. The citation of any reference in the specification is not intended as an admission that the reference is prior art to the present application.
[0044] Many modifications and variations to the illustrative embodiments described herein will be apparent to those skilled in the art from consideration of the specification and practice of the subject technology. Furthermore, other embodiments of the subject technology will be apparent from the specification and practice of the subject technology. It is, therefore, to be understood that such other embodiments are within the scope of the subject technology.
[0045] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having" or the like are open-ended expressions that are intended to denote the presence of stated features, items, elements, components, or the like but do not exclude the presence of one or more other features, items, elements, components, or the like.
[0046] It should be noted that the present application does not specifically describe the means of the art, and is not the focus of the present application.
[0047] The concentration of concentrated sulfuric acid used in the specific embodiment of the present application is 98.3wt%; the concentration of concentrated nitric acid is 68wt%.
[0048] The elemental content of lignite used in the specific embodiment of the present application is: carbon 68.94%, oxygen 25.40%, silicon 2.82%, aluminum 2.19%, iron 0.65%; among them, the carbon element is significantly lower than that of bituminous coal 82.40%, and the oxygen content is significantly higher than that of bituminous coal 12.46%, indicating that the surface of lignite contains rich oxygen-containing functional groups.
[0049] Example 1
[0050] A preparation method of a coal-based red fluorescent carbon dot:
[0051] (1) Dry the lignite to a constant weight, grind and pass through a 200 mesh sieve to obtain a primary coal sample.
[0052] (2) Take 5g of the primary coal sample, mix the primary coal sample with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid and concentrated nitric acid is 1:2) at a mass ratio of 1:1, stir at a speed of 600r / min for 8h, then add 28% ammonia water to adjust the pH of the solution to 7, continue to stir at a speed of 600r / min for 8h, and then filter using a microporous filter membrane to obtain 3g of treated coal sample.
[0053] (3) Put the 3g of treated coal sample obtained in step (2) into a beaker, add 1000mL of deionized water, and stir at a speed of 600r / min for 8h to obtain a lignite mixed solution.
[0054] (4) Put the lignite mixed solution into a hollow cavitation device equipped with a Venturi tube, start the cavitation program, adjust and maintain the flow rate to 100L / h, collect the circulating liquid in the cavitation device after 8h of cavitation stripping, and then filter using a microporous filter membrane with a pore size of 0.45μm to remove residual large particles, to obtain an aqueous solution of coal-based red fluorescent carbon dots.
[0055] The fluorescence curve of the coal-based red fluorescent carbon dots prepared in this example under different excitation lights and the photo under 356 nm ultraviolet light (insert) are shown in Figure 1 .
[0056] As can be seen from Figure 1 , under different excitation light wavelengths, the fluorescence peak of the carbon dots prepared in this example is located in the red light region, and the carbon dot solution shows red color under 540 nm excitation light irradiation.
[0057] The coal-based red fluorescent carbon dot aqueous solution prepared in this example was dropped onto a copper mesh containing a film, and after drying, transmission electron microscope analysis was performed, and the results are shown in Figure 2 .
[0058] As can be seen from Figure 2 , the carbon dots prepared in this example are spherical, with an average size of 3 nm, good dispersity, and no agglomeration phenomenon is found.
[0059] Example 2
[0060] A preparation method of a coal-based red fluorescent carbon dot:
[0061] (1) The lignite was dried to a constant weight, ground and passed through a 200 mesh sieve to obtain a primary coal sample.
[0062] (2) 5 g of the primary coal sample was weighed, mixed with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio of concentrated sulfuric acid and concentrated nitric acid was 1:5) at a mass ratio of 1:2, stirred at a speed of 600 r / min for 8 h, then adjusted the pH of the solution to 7 by adding 28% ammonia water, and continued to stir at a speed of 600 r / min for 8 h. After that, a microporous filter membrane was used to filter to obtain 3 g of treated coal sample.
[0063] (3) The 3 g of treated coal sample obtained in step (2) was placed in a beaker, 1000 mL of deionized water was added, and stirred at a speed of 600 r / min for 8 h to obtain a lignite mixed solution.
[0064] (4) The lignite mixed solution was placed in a hollow cavitation device equipped with a Venturi tube, the cavitation program was started, the flow rate was adjusted and maintained at 100 L / h, and after 8 h of cavitation stripping, the circulating liquid in the cavitation device was collected. After removing the residual large particles by using a microporous filter membrane with a pore size of 0.45 μm, a coal-based red fluorescent carbon dot aqueous solution was obtained.
[0065] Example 3
[0066] A preparation method of a coal-based red fluorescent carbon dot:
[0067] (1) The lignite was dried to a constant weight, ground and passed through a 200 mesh sieve to obtain a primary coal sample.
[0068] (2) Take 5 g of the initial coal sample, mix the initial coal sample with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio of concentrated sulfuric acid and concentrated nitric acid is 1:4) at a mass ratio of 1:2, stir at a speed of 600 r / min for 8 h, then add 28% ammonia water to adjust the pH of the solution to 7, continue to stir at a speed of 600 r / min for 8 h, and then filter using a microporous filter membrane to obtain 3 g of the treated coal sample.
[0069] (3) Place the 3 g of the treated coal sample obtained in step (2) in a beaker, add 1000 mL of deionized water, and stir at a speed of 600 r / min for 8 h to obtain a lignite mixed solution.
[0070] (4) Place the lignite mixed solution in a cavitation device equipped with a Venturi tube, start the cavitation program, adjust and maintain the flow rate to be 200 L / h, collect the circulating liquid in the cavitation device after 8 h of cavitation peeling, filter using a microporous filter membrane with a pore size of 0.45 μm to remove residual large particles, and then obtain a coal-based red fluorescent carbon dot aqueous solution.
[0071] The fluorescent properties of the carbon dots prepared in Examples 2 and 3 are similar to those of Example 1.
[0072] Comparative Example 1
[0073] Preparation of coal-based fluorescent carbon dots:
[0074] (1) Dry the lignite to a constant weight, grind and pass through a 200-mesh sieve to obtain an initial coal sample.
[0075] (2) Take 5 g of the initial coal sample, add the initial coal sample to concentrated sulfuric acid (mass ratio of initial coal sample and concentrated sulfuric acid is 1:2), stir at a speed of 800 r / min for 8 h, then add 28% ammonia water to adjust the pH of the solution to 7, continue to stir at a speed of 800 r / min for 8 h, and then filter using a microporous filter membrane to obtain 3 g of the treated coal sample.
[0076] (3) Place the 3 g of the treated coal sample obtained in step (2) in a beaker, add 1000 mL of deionized water, and stir at a speed of 800 r / min for 8 h to obtain a lignite mixed solution.
[0077] (4) Place the lignite mixed solution in a cavitation device, start the cavitation program, adjust and maintain the flow rate to be 200 L / h, collect the circulating liquid in the cavitation device after 8 h of cavitation peeling, filter using a microporous filter membrane with a pore size of 0.45 μm to remove residual large particles, and then obtain a coal-based fluorescent carbon dot aqueous solution.
[0078] The fluorescence curves of the coal-based fluorescent carbon dot aqueous solution prepared in this comparative example under different excitation lights and the photos under a 360 nm ultraviolet light lamp (insert) are as follows:Figure 3 .
[0079] As can be seen from Figure 3 , the fluorescence peak position of the carbon dots prepared in the present comparative example is concentrated in the blue light region; the aqueous solution of the carbon dots is also blue under excitation of 360 nm ultraviolet light.
[0080] Comparative Example 2
[0081] Preparation of coal-based fluorescent carbon dots:
[0082] (1) Dry the anthracite to a constant weight, grind and pass through a 200 mesh sieve to obtain a primary coal sample.
[0083] (2) Mix the primary coal sample with a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio of concentrated sulfuric acid and concentrated nitric acid is 1:2) at a mass ratio of 1:4, stir at a speed of 800 r / min for 8 h, then adjust the pH of the solution to 7 by adding 28% ammonia water, continue to stir at a speed of 800 r / min for 8 h, and then filter using a microporous filter membrane to obtain 4 g of treated coal sample.
[0084] (3) Put the 4 g of treated coal sample obtained in step (2) into a beaker, add 1 L of deionized water, and stir at a speed of 600 r / min for 8 h to obtain a lignite mixed solution.
[0085] (4) Put the lignite mixed solution into a cavitation device, start the cavitation program, adjust and maintain the flow rate to 200 L / h, collect the circulating liquid in the cavitation device after 8 h of cavitation stripping, and then filter using a microporous filter membrane with a pore size of 0.45 μm to remove residual large particles, to obtain an aqueous solution of coal-based fluorescent carbon dots.
[0086] Under irradiation of excitation light at different wavelengths, the fluorescence peak position of the coal-based fluorescent carbon dots prepared in the present comparative example is concentrated in the blue light region.
[0087] Effect Example 1
[0088] The coal-based red fluorescent carbon dots prepared in Example 1 were used for biological labeling of microorganisms (Shewanella), and the results are shown in Figure 4 .
[0089] The specific method is as follows: the aqueous solution of coal-based red fluorescent carbon dots prepared in Example 1 and Shewanella were added together into a liquid culture medium, and then both were placed in a temperature-controlled shaking bed for culture for 2 days at a temperature of 25°C. New liquid culture medium and aqueous solution of coal-based green fluorescent carbon dots were replaced every day.
[0090] As can be seen from Figure 4As can be seen, the shewanella is rod-shaped, and the length is several microns; the red fluorescence is uniformly distributed in the rod-shaped bacteria, which indicates that the carbon dots are also uniformly distributed in the microbial body. It also indicates that the carbon dots prepared by the application can be applied to the field of microbial biomarkers and imaging.
[0091] The above-described embodiments are only used to describe the preferred modes of the present application, and do not limit the scope of the present application. Without departing from the design spirit of the present application, various modifications and improvements of the technical solutions of the present application made by those skilled in the art shall fall within the protection scope determined by the claims of the present application.
Claims
1. A method for preparing coal-based red fluorescent carbon dots, characterized in that, Includes the following steps: Lignite was added to a mixed solution of concentrated sulfuric acid and concentrated nitric acid to carry out the first mixing reaction. Then, the pH was adjusted to neutral using ammonia water to carry out the second mixing reaction, and a coal sample was obtained. The coal sample was added to water to prepare a lignite mixture, and then the lignite mixture was subjected to cavitation stripping treatment to obtain the coal-based red fluorescent carbon dots.
2. The preparation method according to claim 1, characterized in that, The lignite has a particle size ≤200 mesh.
3. The preparation method according to claim 1, characterized in that, The mass ratio of the lignite to the mixed solution of concentrated sulfuric acid and concentrated nitric acid is 1:1 to 1:
4.
4. The preparation method according to claim 1, characterized in that, The volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1:2 to 1:
10.
5. The preparation method according to claim 1, characterized in that, The rotation speed of the first mixing reaction is 600-1500 r / min, and the time is 8-12 h.
6. The preparation method according to claim 1, characterized in that, The second mixing reaction is carried out at a speed of 600-1000 r / min for 8-10 h.
7. The preparation method according to claim 1, characterized in that, The volume ratio of the coal sample to water is 5-50 g: 1 L.
8. The preparation method according to claim 1, characterized in that, The cavitation stripping process has a flow rate of 1-200 L / h and a duration of 8-10 h.
9. A coal-based red fluorescent carbon dot prepared by the preparation method according to any one of claims 1-8.
10. The application of the coal-based red fluorescent carbon dot of claim 9 in the preparation of fluorescent materials or electron transport materials.
Citation Information
Patent Citations
Method for preparing fluorescent carbon dots by stripping coal gasification slag through hydrodynamic cavitation
CN118026148A
Preparation method of coal-based yellow fluorescent carbon dot aqueous solution
CN119461338A
Process for the preparation of blue-fluorescence emitting carbon dots (CDTS) from sub-bituminous tertiary high sulfur indian coals
US20180251678A1
Process for preparing multicolor, fluorescent carbon quantum dot nanoparticles from coal under mild oxidation conditions
US20220333011A1